Don’t Worry…English is Easy: Strengthening English Writing Skills for SMPN 7 Loa Kulu Students in Kutai Kartanegara Regency: Penguatan Kemampuan Menulis Kosakata Bahasa Inggris Bagi Siswa SMPN 7 Loa Kulu Kabupaten Kutai Kartanegara - Ririn Setyowati; Agra Liz Tantri; Nita Maya Valiantien; Alamsyah Alamsyah (Jurnal Abdita Naturafarm, 2026)
Background: English literacy skills play a vital role in students’ academic and social development. Yet, many junior high school students still struggle with reading and writing due to limited vocabulary and exposure. Objective: This community service program, titled “Don’t Worry, English is Easy,” aimed to strengthen the English literacy skills—particularly reading and writing—of seventh-grade students at SMPN 7 Loa Kulu, Kutai Kartanegara Regency. Methods: The program was conducted by lecturers and students from the Faculty of Cultural Studies, Universitas Mulawarman. The implementation involved observation, documentation, and literacy-based training using contextual materials such as “Introducing Myself,” “My Family,” and “My School.” Results: The findings revealed that students experienced difficulties with spelling and constructing English sentences. Common spelling errors were caused by phonetic interference and limited understanding of English orthography. External factors such as family background, lack of learning facilities, and minimal English exposure outside the classroom also contributed to these challenges. However, students showed increased motivation, confidence, and active participation throughout the training sessions. Conclusion: The program effectively enhanced students’ enthusiasm and engagement in learning English. It is recommended that similar community service programs be implemented continuously through collaboration between universities and schools to strengthen students’ English proficiency holistically.